Student education loan defaults in Malaysia / Haniesah Rafiedah Ahmad Shafuan - Haniesah Rafiedah , Ahmad Shafuan (2019)
This study set out to investigate the following research questions: 1. What are the profile demographic of the borrowers and how it effect on defaulting of the student education loan (NHEFC) in Malaysia? 2. How does the socio-economic of the borrowers influencing the defaulting of the student education loan (NHEFC) in Malaysia? 3. How does the personal attitude of the borrowers’ effect on defaulting of the student education loan (NHEFC) in Malaysia? 4. How do the social-cultural factors effect on defaulting of the student education loan (NHEFC) in Malaysia? It used a mix method approach (qualitative and quantitative). It mainly employed primary data gathered using questionnaire survey (130 respondents from defaulters of education loan) and interviews (2 respondents from NHEFC staff) methods. It employed two methods of data analysis: descriptive statistical method to analyse the demographic information (i.e. percentage) and the inferential statistical method to analyse the research questions and reliability (i.e. Multiple Regression test and Reliability test). The Cronbach’s Alpha (ɑ) is used to measure the reliability. The result of the multiple regression are [f (4, 125) = 3.460, p < 0.05, R² = .100]. It’s also show that 3 from 4 factor are statistically significant predicted respectively demographic, socio-economic, and personal attitude. Therefore, the result show the null hypothesis is rejected while the alternative hypothesis of demographic, socio-economic, and personal attitude was accepted. Its mean there is an association between demographic, socio-economic, and personal attitude factor of the borrower and defaulting of the student education loan (NHEFC) in Malaysia. The variable under demographic factor was positive significant association are marital status, type of educational institution, and graduation. The variable under socio-economic factor is other loan commitment, and personal attitude toward loan repayment have a significant association with loan repayment defaults. The study also found that financial constraints such as a high cost of living, low monthly income and monthly payment management by NHEFC impose difficulties on the borrowers. The study suggests that improvement towards reducing defaults on NHEFC loan can be achieved through the cooperation of three parties involved: the borrower (finding part-time job), NHEFC (improving services), and the government (expanding job market).